Modelling Returns in US Housing Prices – You're the One for Me, Fat Tails - Tamás Kiss; Hoang Nguyen; Pär Österholm (Örebro University School of Business, 2020)
In this paper, we analyse the heavy-tailed behaviour in the dynamics of housing-price returns in the United States. We investigate the sources of heavy tails by estimating autoregressive models in which innovations can be subject to GARCH effects and/or non-Gaussianity. Using monthly data ranging from January 1954 to September 2019, the properties of the models are assessed both within- and out-of-sample. We find strong evidence in favour of modelling both GARCH effects and non-Gaussianity. Accounting for these properties improves within-sample performance as well as point and density forecasts.
Keywords: C22; C52; E44; E47; G17; 330; Non-Gaussianity; GARCH; Density forecasts; Probability integral transform